2017
DOI: 10.1038/s41598-017-09336-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Perivascular Spaces in 7 T MR Image using Haar Transform of Non-local Cubes and Block-matching Filtering

Abstract: Perivascular spaces (PVSs) in brain have a close relationship with typical neurological diseases. The quantitative studies of PVSs are meaningful but usually difficult, due to their thin and weak signals and also background noise in the 7 T brain magnetic resonance images (MRI). To clearly distinguish the PVSs in the 7 T MRI, we propose a novel PVS enhancement method based on the Haar transform of non-local cubes. Specifically, we extract a certain number of cubes from a small neighbor to form a cube group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 33 publications
0
48
0
1
Order By: Relevance
“…Our quantitative PVS mapping and previous works showed that PVS can be mapped from an individual MRI contrast (Ballerini et al, 2018;Boespflug et al, 2018;Comulada, 2015;Del C. Valdes Hernandez et al, 2013;Descombes et al, 2004;Hou et al, 2017;Jung et al, 2018;Park et al, 2016;Ramirez et al, 2015;Wang et al, 2016;Zong et al, 2016). However, it should be noted that in the presence of pathology, additional image sequences (e.g.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Our quantitative PVS mapping and previous works showed that PVS can be mapped from an individual MRI contrast (Ballerini et al, 2018;Boespflug et al, 2018;Comulada, 2015;Del C. Valdes Hernandez et al, 2013;Descombes et al, 2004;Hou et al, 2017;Jung et al, 2018;Park et al, 2016;Ramirez et al, 2015;Wang et al, 2016;Zong et al, 2016). However, it should be noted that in the presence of pathology, additional image sequences (e.g.…”
Section: Discussionmentioning
confidence: 61%
“…EPC also uses a spatial non-local mean filtering technique, which has shown to be effective for mapping PVS (Hou et al, 2017). We noted that even in the high-resolution T2w images of the human connectome project (0.7 mm 3 resolution), it is difficult to detect small PVS (Supplementary Figure 2), while they could be identified with this new technique.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, these methods are called local methods. In recent years, some nonlocal image processing methods have been developed for image denoising, i.e., nonlocalmeans (NL means) [8] and block-matching and 3D filtering (BM3D) [9][10][11][12][13][14][15]. These nonlocal methods attempt to find some of the most similar image blocks, i.e., by implementing block-matching and the weighted means on the blocks [8], or by implementing a 3D transform on a 3D array stacked by similar blocks for enhanced sparsity representation and then for hard-threshold shrinkage on the transformed coefficients 2 Mathematical Problems in Engineering to achieve image denoising [9,10,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%